2019
DOI: 10.3390/ijerph16244955
|View full text |Cite
|
Sign up to set email alerts
|

Association between Exposure to Extreme Temperature and Injury at the Workplace

Abstract: Exposure to extreme temperature is a critical occupational risk factor. This study aimed to investigate the association between exposure to extreme temperatures and injury at the workplace using data from 92,238 workers (46,175 male and 46,063 female) from the 2014 and 2017 Korean Working Condition Survey. Exposure to extremely high or low temperatures, injury experiences, and personal protective equipment (PPE) wearing behavior were investigated using a questionnaire. Logistic regression analyses were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Other working condition factors included in the model show the effects of workplace environment on sick leave: noise, air pollution, extreme temperatures, etc. This was to be expected, because it points in the direction of occupational diseases, in line with several previous studies [44,45].…”
Section: Working Conditionssupporting
confidence: 91%
“…Other working condition factors included in the model show the effects of workplace environment on sick leave: noise, air pollution, extreme temperatures, etc. This was to be expected, because it points in the direction of occupational diseases, in line with several previous studies [44,45].…”
Section: Working Conditionssupporting
confidence: 91%
“…In this study, we found that extreme high temperature was associated with a significant decrease in the risk of PTB at provincial level, although only two prefecture-level cities had found an effect of extreme high temperature on PTB. Epidemiological study has demonstrated that extreme temperature could affect the risk of mortality [31,32], acute myocardial infarction hospital admissions [33], cardiovascular emergency hospitalizations [34], injury [35], infectious diseases (such as, mumps [10], hand-foot-mouth disease [11,36]), etc. In recent years, temperature has been acknowledged as a significant influence factor related to PTB [19,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In her classic, Little Women , 25 Louisa May Alcott said, “Some people seemed to get all sunshine, and some all shadow.” Some workers, especially those working outdoors, are unable to avoid direct sunlight exposure and can be classified as a vulnerable population. 26 27 …”
Section: Introductionmentioning
confidence: 99%